THE DEVELOPMENT OF STUDENTS' LEARNING AUTONOMY IN AN ENGLISH AS A FOREIGN LANGUAGE READING CLASS: Action Research Conducted with the First-Year Students at Politeknik Negeri Bandung. - Merawati, Mv Joyce (2003)
One of the goals of education is to build students' learning autonomy. It, therefore, should be systematically taught and practiced in the subject matters. The present study attempts to investigate the students' problems in reading, the students' strategies to solve their perceived problems and the development of the students' learning autonomy when they learn English as a foreign language in a reading class within two semesters. The data of this study were obtained from three-cycle inductive action research conducted with a class of twenty-four students of Civil Engineering Department of Politeknik Negeri Bandung. The treatments were focused not only on enhancing the students' language learning autonomy but also on reading strategies, especially when constructing meanings of unfamiliar words from contexts. The data were collected from learners' journals, observations, class discussions, and small talks noted during observations. The learners' learning autonomy was explored from the students' learning purpose, knowledge, skills, and willingness. Analyses on the data showed that throughout the treatments, the students' perceived problems moved from general limited language knowledge and language strategies onto various and specific problems. The students' strategies to solve their problems moved from acquiring the language, applying low level cognitive and social strategies to learning the language and applying high-level cognitive strategies and all of which led to managing learning. Exploration, modeling, and practicing direct and indirect strategies have resulted in students' learning autonomy to develop in various degrees and their development was in line with the quality of the students' perceived problems which were associated with their learning purposes, motivation, confidence, language proficiency, learning experiences, and beliefs. The study, then, concludes that learning autonomy in English as a foreign language can be built when learners are able to identify their language problems and have genuine learning purposes. It is, therefore, suggested that to enhance learners' language learning autonomy, various problem-solving tasks with clear instructions and peer models, practices, and various appropriate SALL materials are provided proportionately.